Terapia con células madre en cirrosis (2011)
ABSTRACT: We present a review of the literature on stem cells as therapy for cirrhosis. We emphasize on a description of the present scientific status of the field and its clinical implications. Cell therapy has been proposed in view of the shortage of liver organ donors, and the complications of immunosuppressive therapy. Stem cells may be obtained from different sources such as the blastocyst, bone marrow and even mature hepatocytes. The ability to proliferate and differentiate varies among these cell types. Such variations, among other factors, influence their clinical utility. The safety and feasibility of this technique to improve fibrosis, the ability of the cells to differentiate and replicate, and some clinical parameters have been assessed in both animal models and human beings. Results, although encouraging, should be carefully interpreted. In conclusion, further studies are required on stem cell therapy for cirrhosis because it is still a controversial field.